The Influence of Digital Literacy, Brand Image, and Word of Mouth on Generation Z's Interest in Using the OVO E-Wallet - Nasaruddin Nasaruddin; Tomy Dwi Cahyono (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze the influence of digital literacy, brand image, and word of mouth (WOM) on Generation Z's interest in using the OVO digital wallet in Sumbawa Regency. A quantitative approach with a causal associative method was applied, involving 100 Generation Z respondents (aged 12–27 years) selected through a purposive sampling technique. Data were collected using a 5-point Likert Scale-based questionnaire and analyzed using multiple linear regression using SPSS. The results showed that all three independent variables had a positive and significant effect on OVO usage interest. Digital literacy had the highest regression coefficient (0.462), followed by brand image (0.327) and WOM (0.236). The research model was able to explain 49.6% of the variation in usage interest, with the remainder influenced by other factors outside the model. These findings reinforce the importance of increasing digital literacy, strengthening brand image, and utilizing WOM as strategies to encourage fintech adoption among Generation Z, especially in non-metropolitan areas such as Sumbawa. Practical implications include recommendations for OVO to organize digital education programs, collaborate with local influencers, and develop a community-based referral system